Educational technologies for children and adolescents in palliative and end-of-life care in cancer illness and their families: scope review protocol (Research, Society and Development, 2022)
Objective: To map educational technologies for adolescent and pediatric patients in palliative and end-of-life care due to oncological illness and their families. Methodology: Scope review protocol developed according to the recommendations proposed by the Joanna Briggs Institute and following the PRISMA-ScR checklist. Observational and experimental studies will be included, with quantitative or qualitative approaches, in the electronic databases of Latin American and Caribbean Health Sciences Literature, Spanish Bibliographic Index of Health Sciences and PubMed (MEDLINE/PubMed) via the Virtual Health Library and in the bases: Web of Science, ScienceDirect and Scopus. Gray literature will be selected via Digital Library of Theses and Dissertations, Google Scholar, websites of societies and associations in palliative care and clinical guidelines recognized by government bodies and the World Health Organization. For selection, two reviewers will perform the screening of titles and abstracts, read the full texts and extract data independently. In case of discrepancies, they will be discussed with a third reviewer. The extracted data will be presented in the form of tables and/or charts.